Relation of IL‐6, IL‐13 and IL‐15 gene polymorphisms to the rheumatoid factors, anti‐CCP and other measures of rheumatoid arthritis activity. (17th June 2013) - Pavkova Goldbergova, M.; Nemec, P.; Lipkova, J.; Jarkovsky, J.; Gatterova, J.; Ambrozkova, D.; Vasku, A.; Soucek, M.; Pavek, N.
Summary The aim of the study was to examine the relation between polymorphisms and serum levels of selected cytokines (IL‐6, IL‐13 and IL‐15), production of autoantibodies and factors describing rheumatoid arthritis (RA), such as DAS28 and Total Sharp Score. A total of 156 patients with RA according to the ACR criteria, and 200 control subjects were recruited into the study. The measurements of CRP, anti‐CCP, the presence of rheumatoid factors (RFs), radiographs of both hands with calculation of Total Sharp Score (TSS) and DAS28 were obtained from all patients with RA. In total, five polymorphisms in genes coding cytokines (IL‐6, IL‐13 and IL‐15) were detected. The levels of these selected cytokines were measured in serum using ELISA method. A significant difference in allele frequencies between patients with RA and controls was observed for IL‐15 ‐267C/T polymorphism. A higher prevalence of heterozygote variants of IL‐15 polymorphisms (14035A/T and ‐267C/T) in the RF IgG– and RF IgA–negative subgroups was observed. Furthermore, the association of polymorphisms in gene for IL‐15 with circulating level of IL‐15 (14035A/T and 367G/A) and with total RF and Ig‐specific RFs (‐267C/T) was found. The relation of IL‐15 to RFs IgA, IgM, IgG and the measure of DAS28 was proved. The frequency of the T allele of the IL‐13 polymorphism ‐1112C/T was higher in subgroup with faster progression of the disease (TSS/month ≥ 0.1). In conclusion, we present an association of IL‐15 gene polymorphisms with the RFs including subtypes (RF, IgG, IgA) underlined by the relation of increased IL‐15 levels in circulation to RFs.